Gram-positive aerobic and microaerophilic microorganisms isolated from pathological processes and lesions of horses - J. Bzdil; O. Holy; D. Chmelar (Veterinární Medicína, 2017)
The aim of this study was to characterise the genera and species of Gram-positive aerobic and microaerophilic microorganisms isolated from pathological processes and lesions in horses. In the period 2009-2014, 449 clinical samples from horses were examined. Of these, 229 (51%) were collected from the respiratory tract, 121 (26.9%) from the skin, 40 (8.9%) from the gastrointestinal tract, 40 (8.9%) from the eyes, 8 (1.8%) from the urinary tract, 6 (1.3%) from the musculoskeletal system, 4 (0.9%) from the lymphatic system and 1 (0.2%) from milk. The isolates were presumptively identified phenotypically, and identification was confirmed by molecular phenotypic MALDI-TOF. The most frequently detected strains (n = 330) were Staphylococcus spp., Streptococcus spp., Corynebacterium spp. with prevalence rates of 37.2%, 23.4% and 7.6%, respectively. In addition, 24 other taxa were identified, including Enterococcus spp., Bacillus spp., Trueperella pyogenes, Aerococcus viridans, Dermatophilus congolensis, Lysinibacillus fusiformis, Nocardiopsis alba and Streptomyces spp. Most of these are described as opportunistic pathogens of animals, including horses. Antibiotic susceptibility was tested using the disc diffusion method. Florfenicol and amoxycillin with clavulanic acid were the most effective antibiotics. The susceptibility to florfenicol was 100% for tested strains of Bacillus spp., Lysinibacillus spp., Corynebacterium spp., Dermatophilus congolensis, Streptococcus spp., Enterococcus spp., Aerococcus spp., Nocardiopsis alba and Trueperella pyogenes. The susceptibilities of Staphylococcus aureus and other staphylococci to florfenicol were 96.2% and 98.5% in tested strains, respectively. Amoxycillin with clavulanic acid exhibited 100% effectiveness against Corynebacterium spp., Dermatophilus congolensis, Streptococcus spp., Aerococcus spp., Enterococcus spp., Streptomyces spp., Nocardiopsis alba and Trueperella pyogenes tested strains. The susceptibilities of Staphylococcus aureus, other staphylococci and Bacillus/Lysinibacillus spp. to amoxycillin with clavulanic acid were 89.8%, 98.8% and 20.0% of tested strains, respectively.